Transfiguring Materialities: Relational Abstraction in Byzantium and its Exhibition - Peers, Glenn (Convivium, 2015)
Abstract Analogy in exhibition can reveal aspects of historical art otherwise invisible or neglected, and this paper examines insights gained from the exhibition Byzantine Things in the World (Menil Collection, Houston, tx, 2013). It makes an argument for a particular kind of materiality experienced by Byzantines, broadly speaking, which falls under the rubric of animism. Analysis of conditions of display and experience in the exhibition reveals elements only historically explicable through discussion of Byzantine science, namely alchemy. That “science” took as its premise the essential unity and natural search for perfection in matter. It is the best explanation for creation available to many people in that world, but it also parallels and supports explanations in all fields of inquiry, including theology. In these ways, analogical exhibition manifests insights into a world in which relation among all creation prevailed and in which subjecthood was constantly challenged.